2020
DOI: 10.1080/23311932.2020.1729581
|View full text |Cite
|
Sign up to set email alerts
|

Genotype x environment interaction and yield stability analysis of mung bean (Vigna radiata (L.) Wilczek) genotypes in Northern Ethiopia

Abstract: The experiment was conducted from 2009-2011 cropping seasons. Six mung bean genotypes viz. SML-668, Black bean, Bored, Local Gofa, SML-32 and Local 2-Sheraro were evaluated to early maturing and high yielding genotypes and the design was RCBD with three replications. The combined analysis of variance reviled that there was highly significant variation (p < 0.01) of grain yield among the genotypes, environments and genotype by environment interaction. The genotypic, environmental and the genotype x environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 16 publications
(19 reference statements)
2
17
0
Order By: Relevance
“…A vertical line to the AEC axis indicated that G36, G5, G15, G2, and G9 were stable and good-to low-yielding genotypes. Similar results were reported for cowpea [51] and mungbean [50][51][52][53]. The projection on the AEA was nearer to zero for the genotypes G18 and G29 followed by G31 and G36, indicating the limited interaction between these genotypes and environments.…”
Section: Discussionsupporting
confidence: 83%
“…A vertical line to the AEC axis indicated that G36, G5, G15, G2, and G9 were stable and good-to low-yielding genotypes. Similar results were reported for cowpea [51] and mungbean [50][51][52][53]. The projection on the AEA was nearer to zero for the genotypes G18 and G29 followed by G31 and G36, indicating the limited interaction between these genotypes and environments.…”
Section: Discussionsupporting
confidence: 83%
“…In order to interpret GEI effect in METs, numerous statistical approaches and model have been developed. The additive main effect and multiplicative interaction (AMMI) analysis is one of the best model which widely used for choose of the superior genotypes in barley and other crop plants (Khalili and Pour-Aboughadareh 2016;Paderewski et al 2016;Vaezi et al 2017;Vaezi et al 2018;Baraki et al 2020;Ahakpaz et al 2021). Although this analysis have many advantages in explain GEI, disability of this model in analyzing the structure of the linear mixed-effect model (LMM) caused to arrival new models.…”
Section: Introductionmentioning
confidence: 99%
“…As genotypes, environments and genotypes  environment interactions were significant, it was proceeded to calculate AMMI and GGE stability analysis. Asfaw et al (2012) and Baraki et al (2020) also reported significant GEI in grain yield of mungbean and cowpea genotypes evaluated in different environments.…”
Section: Combined Analysis Of Variancementioning
confidence: 91%
“…Furthermore, environments E2 and E4 are also with longer vector length and are considered as good test environments for selecting widely adapted genotypes. Asfaw et al (2012) and Baraki et al (2020) also used the discriminating representativeness view of the GGE bi-plot to evaluate the testing environments for mungbean and cowpea genotypes, respectively.…”
Section: Discriminating and Representativeness Of The Test Environmentsmentioning
confidence: 99%
See 1 more Smart Citation